(untitled) (REMUNOM, 2025)
This article analyzes the effectiveness of public policies aimed at the inclusion of people with disabilities in the Brazilian labor market, with an emphasis on the role of the Public Labor Prosecution Office (Ministério Público do Trabalho - MPT). The research seeks to understand how the MPT contributes to the implementation of these policies and what challenges still persist. A qualitative approach was used, based on a literature review and document analysis of legislation, institutional reports, and statistical data from IBGE and the MPT itself. The results indicate that, although there have been significant legislative advances, such as the Quota Law and the Statute of Persons with Disabilities, cultural, structural, and institutional barriers still hinder the full inclusion of these individuals in the workforce. The MPT’s actions through inspections, educational campaigns, and guidance to companies are essential for ensuring compliance with these regulations. It is concluded that the active participation of persons with disabilities goes beyond mere legal compliance and requires continuous and coordinated efforts among the State, businesses, and civil society to foster a truly inclusive environment.